2020
DOI: 10.1186/s12875-020-01155-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on professional identity and related factors among Chinese general practitioners: a National Cross-sectional Study

Abstract: Background: Studies on professional identity and related factors among Chinese general practitioners (GPs) are unavailable. The objective of this study was to investigate the professional identity level of GPs in China and explore factors associated with GPs' perceptions of their professional identity. Methods: A multistage stratified random sampling method was used to collect data with a structured selfadministered questionnaire from 3236 GPs working in community health service institutions (CHIs) in China be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 43 publications
3
12
1
Order By: Relevance
“…Additionally, there was no statistically significant correlation between nurse managers' professional identity and their age at the pretest and follow-up phases. This is consistent with Li et al. (2020) who found a statistically significant relationship between professional identity and age.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, there was no statistically significant correlation between nurse managers' professional identity and their age at the pretest and follow-up phases. This is consistent with Li et al. (2020) who found a statistically significant relationship between professional identity and age.…”
Section: Discussionsupporting
confidence: 91%
“…This can be explained by the fact that all the subjects have a bachelor's degree in nursing. Along the same line, (Li et al, 2020) concluded that Chinese general practitioners (GPs) have a higher level of professional identity. Mohtashami et al (2015) also reported that more than half of the nursing staff had a good professional identity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the PI of nursing undergraduates in China is relatively low [ 12 , 13 ], and the PI score in this study was in a middle level. Nursing student's future career positioning is not clear enough, and there is also a lack of specific interventions to improve the PI.…”
Section: Discussionmentioning
confidence: 53%
“…In order to capture a representative sample, we approached potential participants who were on duty during the survey period. In total, 3244 urban GPs were invited to complete a self-administered questionnaire (Additional file 1) [24]. Of those invited participants, 3236 (99.75%) returned valid questionnaires for data analyses.…”
Section: Study Population and Samplingmentioning
confidence: 99%